Blood pressure reduction as a result of the Boxville Vitals partnership. Issue 8 (6th June 2022) - Wu, Anna; Snell, Brittney Nicole; Younge, Jewel Sophia
Abstract: Introduction: Boxville Vitals is a blood pressure and blood glucose testing site in Chicago Illinois facilitated by students and faculty of the University of Illinois Chicago College of Pharmacy during the weekly arrival of a mobile produce grocer to Boxville Marketplace. Boxville Vitals focuses on trust‐building and accessibility of care. Objectives: The primary objective was to build community engagement by increasing weekly participation and secondarily, to observe a change in blood pressure among returning patrons. Methods: Blood pressure and blood glucose testing was offered from August through October 2021. Patients were "nudged" to care through a "stress‐free" approach. No diagnoses were made. Only "new" vs "returning" status was recorded. Weekly attendance was used to measure engagement. A Mann‐Whitney U test was performed using Prism to compare mean reductions in blood pressures among "new" and "returning" patrons. Results: Of 84 results collected, 65 were blood pressures; 48 new and 17 returning results. The 8‐week program elicited robust engagement; 21% returned for follow‐up. A mean reduction of 13.95 mm Hg in systolic blood pressure (95% confidence interval, P < .02) was found between the two groups. Conclusion: Boxville Vitals shows that an intrinsically motivated population can be meaningfully served by bringing care within reach. Clinically significant reductions in systolic blood pressures were found.